Cost Sharing in Collective Contests - Shmuel Nitzan; Kaoru Ueda (Center for Economic Studies and ifo Institute (CESifo), 2014)
This paper studies collective contests with endogenous cost sharing, general effort costs and intra-group heterogeneity of prize-valuation. Our objective is to clarify the relationship between cost sharing, intra-group heterogeneity within the competing groups and the elasticity of the marginal cost of effort incurred by the individual contestants. We also wish to stress the significance of intra-group heterogeneity in comparing the performance of cost sharing relative to prize sharing as a means of resolution of the collective action problem faced by the competing groups and present preliminary results for such comparisons. Our main results ascertain that unequal valuations of the contested prize within a group tend to result in a low degree of cost sharing. That is, intra-group heterogeneity prevents the group from establishing strong cost-sharing selective incentives.
Keywords: D70; D71; D72; 330; collective contest; selective incentives; cost sharing; intra-group heterogeneity; elasticity of marginal effort costs; prize sharing